Semantic versus perceptual priming: dissecting their impact on intuitive judgments of semantic coherence - Sweklej, Joanna; Balas, Robert (Frontiers in Psychology, 2024)
This research explores the mechanisms underlying the intuitive processing of semantic coherence, focusing on the effects of semantic and perceptual priming on semantic coherence detection. Two studies examined how these priming types influence individuals' abilities to discern semantic incoherence. In Study 1, we used solutions to semantically coherent triads as primes, finding that such priming significantly improves participants' accuracy and confidence in identifying incoherent elements within word tetrads. These results corroborate the hypothesis that intuitive judgments in linguistic tasks are closely tied to the processing fluency elicited by semantic connections. In Study 2, we show that perceptual priming does not significantly enhance accuracy, albeit it does increase the confidence with which individuals make their judgments. Distinct effects of semantic and perceptual priming on intuitive judgments highlight the complex interplay between processing fluency and affect in shaping intuitive judgments of semantic coherence. We discuss the nuanced roles of semantic and perceptual factors in influencing the accuracy and confidence of intuitive decisions.